Autologous Bone Marrow‐Derived Mesenchymal Stromal Cells for the Treatment of Allograft Rejection After Renal Transplantation: Results of a Phase I Study. (24th January 2013) - Reinders, Marlies E.J.; de Fijter, Johan W.; Roelofs, Helene; Bajema, Ingeborg M.; de Vries, Dorottya K.; Schaapherder, Alexander F.; Claas, Frans H.J.; van Miert, Paula P.M.C.; Roelen, Dave L.; van Kooten, Cees; Fibbe, Willem E.; Rabelink, Ton J.
Abstract : Mesenchymal stromal cells (MSCs) are an interesting candidate to aid in the long‐term survival of transplanted kidneys, because of their immunosuppressive and regenerative properties. This phase I study was the first to investigate the effects of MSCs in allograft rejection and fibrosis. Findings support the potential of MSCs as a novel cell therapy to prevent allograft rejection and interstitial fibrosis/tubular atrophy. The observed systemic immune suppression implies that careful monitoring of opportunistic viral infection is needed. Abstract : Despite excellent short‐term results, long‐term survival of transplanted kidneys has not improved accordingly. Although alloimmune responses and calcineurin inhibitor‐related nephrotoxicity have been identified as main drivers of fibrosis, no effective treatment options have emerged. In this perspective, mesenchymal stromal cells (MSCs) are an interesting candidate because of their immunosuppressive and regenerative properties. Of importance, no other clinical studies have investigated their effects in allograft rejection and fibrosis. We performed a safety and feasibility study in kidney allograft recipients to whom two intravenous infusions (1 million cells per kilogram) of autologous bone marrow (BM) MSCs were given, when a protocol renal biopsy at 4 weeks or 6 months showed signs of rejection and/or an increase in interstitial fibrosis/tubular atrophy (IF/TA). Six patients received MSC infusions. Clinical and immune monitoring was performed up to 24 weeks after MSC infusions. MSCs fulfilled the release criteria, infusions were well‐tolerated, and no treatment‐related serious adverse events were reported. In two recipients with allograft rejection, we had a clinical indication to perform surveillance biopsies and are able to report on the potential effects of MSCs in rejection. Although maintenance immunosuppression remained unaltered, there was a resolution of tubulitis without IF/TA in both patients. Additionally, three patients developed an opportunistic viral infection, and five of the six patients displayed a donor‐specific downregulation of the peripheral blood mononuclear cell proliferation assay, not reported in patients without MSC treatment. Autologous BM MSC treatment in transplant recipients with subclinical rejection and IF/TA is clinically feasible and safe, and the findings are suggestive of systemic immunosuppression.